Revolutionizing Industries: AI and Blockchain Solutions for Supply Chain and Insurance - Karthik Muccha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of artificial intelligence and blockchain technologies in revolutionizing supply chain management and insurance industries. The article examines three groundbreaking platforms: AI-driven predictive supply chain management, blockchain-as-a-service for supply chain transparency, and AI-powered insurance risk assessment. Through a detailed examination of real-world implementations, the article highlights how these technologies enable organizations to shift from reactive to proactive operations, enhance transparency, and deliver personalized risk assessments. It investigates the technical architecture, implementation considerations, and future directions of these platforms, emphasizing the importance of robust infrastructure, data governance, and change management. The article reveals how the convergence of AI's predictive capabilities with blockchain's secure, distributed architecture creates robust, scalable solutions for modern business challenges. It demonstrates that organizations implementing these technologies systematically achieve significant improvements in operational efficiency, risk management, and customer service while highlighting the critical factors necessary for successful digital transformation.
Keywords: Digital Transformation; Supply Chain Analytics; Blockchain Technology; Risk Assessment; Artificial Intelligence